Pertanggungjawaban Pidana Pemberi dan Penerima Suap dalam Proyek Pengerjaan Pembangunan Infrastruktur: Studi Putusan Nomor 438 K/Pid.Sus/2021 - Ferdy Safriadi; Guntur Rambey (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Bribery in infrastructure projects is a form of corruption that undermines the legal order and public trust in government institutions and state administrators. In this study, the bribe giver is considered to play a role in influencing the decision or action of public officials, while the bribe receiver is considered to have abused his authority. This research uses normative research methods, commonly referred to as legal research techniques, positive legal research techniques, doctrinal legal research techniques, and pure legal research techniques, used in this research. Legal research that focuses on written laws or regulations (law in books) or legal research based on social norms and regulations is known as normative legal research. bribe givers and recipients have criminal liability regulated in law number 31 of 1999 concerning the eradication of criminal acts of corruption amended by law number 20 of 2001. Article 5, both the giver and receiver of a bribe are considered to be the perpetrators of a criminal offence. a bribe giver who offers or gives something to a state official to influence a decision that will benefit him or her or someone else can be sentenced. Enforcement is carried out through investigation, investigation, prosecution, and trial of bribery cases. One method that is often used is the Hand Capture Operation (OTT) by the KPK, which has successfully uncovered many major bribery cases among state officials,